Safety of the Mobile Stroke Unit: A Descriptive Review and Results of Radiation Monitoring. Issue 8 (August 2021) - Susa, Stephen; Rahmani, Redi; Conover, David; Carr, Samuel; Ellens, Nathaniel; Proper, Diana; Le Roux, Peter; Catapano, Joshua; Srinivasan, Visish; Bhalla, Tarun
Abstract : Supplemental Digital Content is available in the text.